0.29(x+50)-6=0.4(3x+20)

Simple and best practice solution for 0.29(x+50)-6=0.4(3x+20) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.29(x+50)-6=0.4(3x+20) equation:


Simplifying
0.29(x + 50) + -6 = 0.4(3x + 20)

Reorder the terms:
0.29(50 + x) + -6 = 0.4(3x + 20)
(50 * 0.29 + x * 0.29) + -6 = 0.4(3x + 20)
(14.5 + 0.29x) + -6 = 0.4(3x + 20)

Reorder the terms:
14.5 + -6 + 0.29x = 0.4(3x + 20)

Combine like terms: 14.5 + -6 = 8.5
8.5 + 0.29x = 0.4(3x + 20)

Reorder the terms:
8.5 + 0.29x = 0.4(20 + 3x)
8.5 + 0.29x = (20 * 0.4 + 3x * 0.4)
8.5 + 0.29x = (8 + 1.2x)

Solving
8.5 + 0.29x = 8 + 1.2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1.2x' to each side of the equation.
8.5 + 0.29x + -1.2x = 8 + 1.2x + -1.2x

Combine like terms: 0.29x + -1.2x = -0.91x
8.5 + -0.91x = 8 + 1.2x + -1.2x

Combine like terms: 1.2x + -1.2x = 0.0
8.5 + -0.91x = 8 + 0.0
8.5 + -0.91x = 8

Add '-8.5' to each side of the equation.
8.5 + -8.5 + -0.91x = 8 + -8.5

Combine like terms: 8.5 + -8.5 = 0.0
0.0 + -0.91x = 8 + -8.5
-0.91x = 8 + -8.5

Combine like terms: 8 + -8.5 = -0.5
-0.91x = -0.5

Divide each side by '-0.91'.
x = 0.5494505495

Simplifying
x = 0.5494505495

See similar equations:

| (x+3)+(y+6)=46 | | 4.2d=-10.5 | | 7k+5=5(1-7k) | | 3(x-4)+4(x+3)= | | 48-2x=x | | .25x-0.75=-0.25x+3.25 | | x-16+2x-85+.5x+8=180 | | 7-14x=15x-16 | | 3x+y=78 | | -27t=-21.6 | | 14x^2+7x-21=0 | | -5y=8.5 | | 5t^2+15t+10=0 | | 3k-k+3=k-7 | | -4.72x=65 | | -4x^2+4x-7=0 | | 12+5z=13+5z | | 14-4t=2(17-t) | | 2(48)=x | | (x-1)(x+5)=x+4x-2 | | 2(x)=48 | | 0.089x-0.32+0.001(5-x)=0.231 | | -37=8y | | 2(h-5)h=h-10 | | 8-3x=-4x-12 | | 2(x)-8=40 | | 28-5t=2t | | 4-2=y+10 | | 3x+2=2x-11 | | 2y^2-3y-20=0 | | 5x-2=6x+3 | | 15x^2-28x-32=0 |

Equations solver categories